Adoption of Public Sector Innovation in Jakarta Kini (JAKI) Application - Marselinus, Ruben Zefanya; Wijaya, Komang Adi Sastra (Spirit Publik: Jurnal Administrasi Publik, 2024)
Innovation in the public sector is an important element in improving and enhancing higher quality public services. Public sector tends to have problems with things such as efficiency, effectivity, corruption, slow responds and many others. The DKI Jakarta Government has made innovations in the public sector, namely the JAKI application which integrates various public services and public information into one application. The problem found in the JAKI application is the low adoption of innovations or the use of JAKI application innovations by the community, coupled with a decrease in the number of users in 2023. This research used qualitative methods, data obtained by interview, observation and documentation. The purpose of this research is to identify which indicators of Rogers innovation attributes cause the low adoption rate of JAKI application. The results of this study indicate that JAKI innovation has fulfilled the innovation attributes of relative advantage, compatibility, and observability. In the complexity indicator, the JAKI application is still constrained by the application that still occurs errors. Furthermore, in terms of trialability indicator, many people do not know the JAKI application and have never used or tried the JAKI application. In addition, the JAKI application was launched without prior testing and lack of direct socialization. Therefore, it can be concluded that the adoption of JAKI application is lacking due to complexity and trialability indicator.